Influence of homogenization on physical properties of model coffee creamers stabilized by quillaja saponin. (September 2017) - Chung, Cheryl; Sher, Alexander; Rousset, Philippe; McClements, David Julian
Abstract: There is a growing demand for use of natural ingredients in food manufacturing. This study utilized a natural emulsifier, quillaja saponin (1%) to fabricate non-dairy model creamer emulsions (containing 10% medium chain triglycerides oil). Varying homogenization conditions, ranging from a high-shear mixer to passing through a microfluidizer at 20, 000 psi, were applied to fabricate emulsions. The effect of particle size on the appearance, tristimulus color coordinates, and electrical characteristics of the model creamers and white coffee drinks were investigated. The average droplet size varied from 0.2 to 16 μm. All model creamers had whitish milk-like appearance and the white coffee solutions had light brown color. All systems were physically stable except for the systems with largest oil droplets (1.8 and 16 μm), which had creaming. The lightness, L* (whiteness) of the model creamer and the white coffee increased with decreasing oil droplet size, as smaller droplets scatter more light. Decreasing the oil droplet size led to lower zeta potential (from − 73 to − 54 mV) due to lesser negative charge group accumulated on the interfacial layer of the droplets. The oil droplets were also found to be stable to aggregation in hot acidic coffee solutions prepared using model hard water. Overall, this study found that oil droplets stabilized with natural plant-based surfactant have potential for application in liquid coffee creamers and their stability and whitening power were dependent on the droplet size. Graphical abstract: Highlights: Non-dairy model coffee creamers were prepared using plant-extracted quillaja saponin as emulsifier. Increasing homogenization pressure and passes produced smaller oil droplets and whiter creamers. The model creamers were stable to aggregation and able to whiten coffee after added to acidic hot coffee solutions. These creamers are suitable for consumers requiring alternatives to synthetic or animal-based ones.